2016
DOI: 10.1186/s13063-016-1188-5
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and processing speed training in schizophrenia: study protocol for a randomized controlled trial

Abstract: BackgroundIn most domains of cognition, individuals with schizophrenia are generally found to be one standard deviation below the mean of the controls. As a result, examining the impact of cognitive remediation in individuals with schizophrenia has been a burgeoning area of research. However, the state of the literature remains unclear as to which domains of cognition should be targeted to produce the most widespread and durable benefits for individuals with schizophrenia. One suggestion is that targeting lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 98 publications
1
11
0
4
Order By: Relevance
“…Processing speed appears to be particularly important to measure in UHR individuals, also for screening purposes (González‐Blanch et al., 2011), because it may capture the generalized impairment. From a treatment perspective, our study may provide a rationale for targeting this apparently domain‐general neurocognitive mechanism, using behavioral and/or pharmacological interventions to boost neurocognitive processing efficiency (Brébion et al., 2014; Cassetta & Goghari, 2016; Cassetta et al., 2019; Takeuchi & Kawashima, 2012). Thus, a double‐blind randomized clinical trial has shown that UHR individuals receiving processing speed training exhibit improvement not only in processing speed but also in social functioning (Choi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Processing speed appears to be particularly important to measure in UHR individuals, also for screening purposes (González‐Blanch et al., 2011), because it may capture the generalized impairment. From a treatment perspective, our study may provide a rationale for targeting this apparently domain‐general neurocognitive mechanism, using behavioral and/or pharmacological interventions to boost neurocognitive processing efficiency (Brébion et al., 2014; Cassetta & Goghari, 2016; Cassetta et al., 2019; Takeuchi & Kawashima, 2012). Thus, a double‐blind randomized clinical trial has shown that UHR individuals receiving processing speed training exhibit improvement not only in processing speed but also in social functioning (Choi et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The full rationale and methodology of the present study was previously published (Cassetta and Goghari, 2016) and registered online at ClinicalTrials.gov (registration number: NCT02478827). The current study was a randomized controlled trial (RCT) that employed a parallel design with a 1:1:1 allocation ratio.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described (Cassetta and Goghari, 2016), all participants were administered the following measures at pre- and post-assessment: three measures of WM (N-Back, maintenance and manipulation task, and digit span), two measures of PS (symbol search and color naming from the Delis–Kaplan Executive Function System [DKEFS]), two measures of fluid intelligence (Raven's Standard Progressive Matrices [RSPM] and Cattell's Culture Fair Test [CCFT]), three measures of executive functioning (EF; DKEFS Color-Word Interference Test [CWIT]-Inhibition Scale, DKEFS CWIT-Switching Scale, DKEFS Trail Making Test [TMT]-Switching Subtest), two measures of social cognition (The Hinting Task and the Geneva Emotion Recognition Test [GERT]), four measures of daily functioning/symptomatology (the Cognitive Failures Questionnaire [CFQ], UCSD Performance-Based Skills Assessment Brief [UPSA Brief], Social and Occupational Functioning Assessment Scale [SOFAS], and the Positive and Negative Syndrome Scale [PANSS]), and two measures of beliefs regarding cognition (Need for Cognition Scale and Theories of Intelligence Scale). The primary outcome measures (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…As Funções Executivas (FEs) são mecanismos A memória operacional é responsável pelo armazenamento, organização e manipulação de múltiplas informações em um curto espaço de tempo (Cassetta et al, 2016;Müller et al, 2002), portanto, essencial para o planejamento, aprendizagem e compreensão de qualquer interação de linguagem, seja ela oral ou gráfica (Diamond, 2012).…”
Section: Funções Executivasunclassified
“…Grupos com TDAH exibiram comprometimento significativo em todas as tarefas de FEs. Os efeitos mais fortes e consistentes foram obtidos nas medidas de capacidade inibitória e memória de operacional.Os estudos deCastellanos et al,2006;Matthews et al, 2014) enfatizaram a importância das questões de heterogeneidade para a a definição de conceitos e abordagens atuais no TDAH ao apontar que, embora exista um padrão de compromentimento das funções executivas nos portadores, a apresentação dessa deficiência varia drasticamente.As funções executivas são apontadas como fator principal nas dificuldades sociais, emocionais e acadêmica das crianças com TDAH (Barkley,2005) e determinantes na diminuição de seus sintomas quando estimuladas em treinamentos e intervenções que envolvam atividade motora. As práticas de intervenção serão mais eficazes se propuserem estimulação simultânea das múltiplas funções que costumam estar deficientes em crianças com TDAH…”
unclassified